2010
DOI: 10.1002/biof.104
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between maternal serum coenzyme Q10 levels and infant birth weight

Abstract: The purpose of this study was to examine the relationship between the level of maternal serum coenzyme Q10 (CoQ10), which is a lipid-soluble antioxidant, maternal body weight gain, fat mass gain, and infant birth weight. A longitudinal observational study was conducted with 50 healthy pregnant women (average age: 31.1 years, average body mass index (BMI): 21.3 kg/m(2) at prepregnancy) at each trimester. CoQ10 levels were measured by high performance liquid chromatography. Maternal weight and body composition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…have reported that, in male Wistar rats, consumption of a diet supplemented with 1000 IU vitamin E/kg diet and 0.16% w/w α‐lipoic acid results in plasma levels of vitamin E that are consistent with those reported in pregnant women 33 . Similarly, rats consuming a diet supplemented with 0.2% CoQ10 have serum CoQ10 levels that are representative of human serum levels in pregnant women 34,35 . Information regarding serum levels of α‐lipoic acid in humans is difficult to obtain owing to the short half‐life of this compound 36 .…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…have reported that, in male Wistar rats, consumption of a diet supplemented with 1000 IU vitamin E/kg diet and 0.16% w/w α‐lipoic acid results in plasma levels of vitamin E that are consistent with those reported in pregnant women 33 . Similarly, rats consuming a diet supplemented with 0.2% CoQ10 have serum CoQ10 levels that are representative of human serum levels in pregnant women 34,35 . Information regarding serum levels of α‐lipoic acid in humans is difficult to obtain owing to the short half‐life of this compound 36 .…”
Section: Methodsmentioning
confidence: 81%
“…33 Similarly, rats consuming a diet supplemented with 0.2% CoQ10 have serum CoQ10 levels that are representative of human serum levels in pregnant women. 34,35 Information regarding serum levels of a-lipoic acid in humans is difficult to obtain owing to the short half-life of this compound. 36 We chose to provide a combination of antioxidants because antioxidants function optimally as reduction-oxidation (redox) couples 37 and to target different pathways of oxidative stress.…”
Section: Maintenance and Treatment Of Animalsmentioning
confidence: 99%
“…Maternal serum coenzyme Q10 levels were positively correlated with maternal weight gain (P , 0.05) and fat mass gain (P , 0.05), as well as positively correlated with fetal growth (P , 0.05). 71 This study did not investigate differences in dietary intake between the groups.…”
Section: Next Generation Antioxidants For Prenatal Nutrition Coenzymementioning
confidence: 98%
“…Coenzym Q10, das Schlüsselenzym der mitochondrialen Atmungskette, nimmt hier eine Sonderstellung ein. Ausreichende maternale Coenzym-Q10-Serumspiegel sind assoziiert mit gutem fetalen Wachstum [18] und reduziertem Risiko für Schwangerschaftskomplikationen wie Präeklampsie [19]. In einer doppelblinden Interventionsstudie mit 200 mg Coenzym Q10/d bei 235 Patientinnen mit erhöhtem Risiko für Präeklampsie konnte das Risiko der Krankheitsentstehung signifikant reduziert werden [20].…”
Section: Mitochondriopathien Als Ursacheunclassified